PENGARUH STRATEGI INQUIRI MINDS WANT TO KNOW TERHADAP KEAKTIFAN SISWA PADA MATA PELAJARAN IPS KELAS IV SDN 250 MALUKU TENGAH - Meute, Sulce; Mahananingtyas, Elsinora; Ritiauw, Samuel Patra; Ritiauw, Leonid (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2023)
Based on the results of initial observations at SDN 250 Central Maluku on January 27 2023, several problems were found in the learning process, especially in creating active learning, the lack of interaction between teachers and students resulted in learning not being achieved optimally. The problems that occur in class IV at SDN 250 Central Maluku are that students do not concentrate in learning, and there is a lack of student activity in the learning process. It was found that out of 10 class IV students, there were 4 students who were always active in the learning process, while the other 6 students were less active in teaching and learning process. These problems result in learning objectives that cover several student competencies being less achievable, including cognitive and affective aspects, so there is a need to implement new strategies, one of which is the inquiry minds want to know learning strategy. In this case, the researcher applied the learning strategy inquiry minds want to know. This strategy is considered to be able to attract students' attention and interest in learning and can increase student activity in the learning process, especially in Social Sciences subjects. The approach used in this research is a quantitative approach. This type of research was carried out using a one group Pretest-Posttest design with a one sample design carried out twice. The sample in question is one class as a sample from the entire population, namely class IV at SD Negeri 250 Central Maluku. This sample is a class that was treated by examining the influence of the inquiry minds want to know learning strategy on the learning process in Class IV SDN 250 Central Maluku. Keywords: Inquiry mind want to know strategy, student activity